SEROLOGICAL SURVEY OF TOXOPLASMA GONDII IN DOGS AND CATS - Faiz Ahmad, Azhar Maqbool, Ashar Mahfooz and Sikandar Hayat (Pakistan Veterinary Journal, 2001)
A serological survey for Toxoplasma gondii in dogs (n=40) and cats (n= 10) was conducted by using a Latex agglutination test (LAT). The overall seroprevalence of T. gondii in canines was 50%. Out of total 9 dogs were found seropositive at 1:256, giving an evidence of presence of infection. The seroprevalence of T. gondii in canines was inversely related to the age i.e., 52% at 6 months and 33.33% at 4 years of age. Little variation in seropositivity was observed between males (57.89%) and females (42.85%) or between exotic (46.15%) and local (57.14%) breeds. However, tremendous variation in seropositivity was found between stray dogs (78.57%) and pet dogs (34.61 %) and between dogs having close contact with cats (50%) and without contact {16.16%). Out of the tested bitches, 66.66% were seropositive, mostly at I: 16 indicating residual immunity. The overall seroprevalence of T. gondii in cats was 60%, three at screening dilution of 1:256, suggesting recent exposure to Toxoplasma. The seroprevalence of T. gondii in cats was directly related to age. A significant difference in seropositivity was observed between stray cats (66.66%) and indoor cats (57.14%) and between females (70%) and males (40%).The seropositive rate in local breeds of cats was high (66.66%) as compared with exotic (50%). This test might give false positive results due to interfering factors (rheumatoid factor and IgG class antibodies). So it is not a "Gold standard" test for the concrete diagnosis of toxoplasmosis.